The Influence Of Financial Performance Indonesian Government Bank on Share Return from 2013-2016 - Sunarya, I Wayan (Manajemen dan Kewirausahaan; Vol 9 No 1 (2018): Published in January 2018, 2018)
The performance of financial statements will show the level of productivity within a company. For that especially in the banking world, the performance of its financial statements can be seen from Economic Value Added (EVA) and Market Value Added (MVA). In this study analyzed MVA and EVA are state-owned banks consisting of Bank Tabungan Negara (BTN), Bank Negara Indonesia (BNI), Bank Mandiri and Bank Rakyat Indonesia (BRI). From the research result, it is known that Indonesian government bank in giving share return to shareholders is not influenced by Economic Value Added (EVA) and Market Value Added (MVA).